Development of the 21st Century Leader Attribute Indicators of Air Cadets (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objectives of this quantitative research were to: (1) study the conceptual framework; (2) identify the element and 21st century leader attribute indicators of air cadet; (3) verify the structural straightness of 21st century leader attribute indicators of air cadet measurement model.  A sample of 460 was stratified randomly chosen from executive position commissioned officers affiliated directly to the Air Force, at the division director level and above (Group Captain and above).  The instrument was a questionnaire created by the researcher with the reliability level of 0.98.  Usable questionnaire copies of 386 or 83.99 percent were returned.  The statistics for this research were: mean, standard deviation, content analysis, and confirmatory factor analysis. The results of the research were as follows:  The 21st century leader attribute indicators of air cadet consisted of 3 aspects with 19 indicators as follow; First aspect was Personality attribute consisted of 7 features: integrity, loyalty, courage, enthusiasm, dependability, tact, and bearing. Follow by Ability attribute consisted of seven features: initiative, knowledge, discretion, decisiveness, holistic problem-solving, endurance and vision. Last, Social skill attribute consisted of five features: interpersonal, Selflessness, justice, understand of differences, and empowering subordinates.  The results of the confirmatory inspection showed that 21st century leader attribute indicators of air cadet were consistent with the empirical data by considering the value of Goodness of fit: c2=112.94, df = 94, p-value 0.89; Relativec2 = 0.14; GFI = .97; AGFI = .95, RMR = .02; SRMR = .02, RMSEA = .02.  The weight of each factor was between 0.91-0.94, and the standard weight of each indicator was between 0.59-0.91.